ANALISIS DISPARITAS EKONOMI DAERAH PESISIR PULAU JAWA - Atika Fatimah (Center for Economic Studies Universitas Katolik Parahyangan, 2020)
This research aim to determine the value of economic disparity in the northern and southern coastal Java Island. The approach of research is quantitative. The data of research is secondary data which is consist of provincial and district GRDP and total population. The analysis method used to calculate the value of disparity is Entropy Theil Index. The results of the research is average value of Entropi Theil Index in the northen coastal Java Island at 0,0085. This indicates that the southern coastal is more distributed than the northen coastal of Java Island because the value of Entropi Theil Index is smaller.